2012
DOI: 10.1093/humupd/dms044
|View full text |Cite
|
Sign up to set email alerts
|

Why do singletons conceived after assisted reproduction technology have adverse perinatal outcome? Systematic review and meta-analysis

Abstract: Subfertility is a major risk factor for adverse perinatal outcome in ART singletons, however, even in the same mother an ART singleton has a poorer outcome than the non-ART sibling; hence, factors related to the hormone stimulation and/or IVF methods per se also may play a part. Further research is required into mechanisms of epigenetic modification in human embryos and the effects of cryopreservation on this, whether milder ovarian stimulation regimens can improve embryo quality and endometrial conditions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
424
4
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(479 citation statements)
references
References 105 publications
28
424
4
11
Order By: Relevance
“…However, when taking infertility into account, the new adjusted OR became 1.01 (95 % CI 0.82-1.23). Our study on a large number of pregnancies (2414) and deliveries (1867) all from a single center, with a nearly complete follow up and inclusive of complications at birth and at any stage of gestational age, confirms that infertility in itself is a risk factor for increased incidence of congenital anomalies [28,31,[35][36][37].…”
Section: Discussionsupporting
confidence: 64%
“…However, when taking infertility into account, the new adjusted OR became 1.01 (95 % CI 0.82-1.23). Our study on a large number of pregnancies (2414) and deliveries (1867) all from a single center, with a nearly complete follow up and inclusive of complications at birth and at any stage of gestational age, confirms that infertility in itself is a risk factor for increased incidence of congenital anomalies [28,31,[35][36][37].…”
Section: Discussionsupporting
confidence: 64%
“…In fresh donor cycles, recipients have hormone levels more comparable to those in a natural conception cycle, which may in part explain the improved rates of implantation, clinical pregnancy, and live births [38], as well as lower rates of LBW, SGA [8], and preterm birth [5]. Results of clinical studies and meta-analyses of IVF pregnancies indicate the risks for SGA, preterm birth, LBW, antepartum hemorrhage, and perinatal mortality are significantly reduced with frozen compared to those with fresh embryo transfers [2,[39][40][41][42]. The risk of prenatal bleeding, placental complications, and postpartum hemorrhage has been shown to be higher in both subfertile and IVF pregnancies compared to those conceived spontaneously [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that children born from in vitro fertilization (IVF) are more likely to be born smaller and earlier, even when limited to singletons [1][2][3]. Prior studies have also consistently reported an excess of large-for-gestational age (LGA) birthweights among children born from frozen embryos; [4][5][6][7][8][9][10][11][12] longer embryo culture of fresh embryos has also been implicated as a potential cause of LGA [13].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale to use so-called segmented-ART treatment has been the avoidance of iatrogenic complications related to controlled ovarian stimulation (COS), such as, ovarian hyperstimulation syndrome (OHSS) and premature progesterone rise [3,5]. In the latter case, deferring fresh transfer, freezing all embryos, and transferring frozen-thawed embryos in a subsequent physiologically normal cycle has been shown to potentially result in improved embryo implantation and placentation and consequently improved perinatal and neonatal outcomes [1][2][3][6][7][8][9][10][11][12][13]. However, segmented treatment also has complications, i.e., the management of an increased number of confounding variables and an increase in the treatment duration.…”
Section: Introductionmentioning
confidence: 99%